Comparative analysis of microRNA expression profiles of adult Schistosoma japonicum isolated from water buffalo and yellow cattle - Yu, Xingang (Parasit Vectors, 2019)
BACKGROUND: Yellow cattle and water buffalo are important natural reservoir hosts and the main transmission sources of Schistosoma japonicum in endemic areas of China. The worms from the two hosts have marked differences in general worm morphology and ultrastructure, gene transcription and protein expression profiles. RESULTS: To investigate microRNAs (miRNAs) involved in the regulation of schistosome development and survival, we compared miRNA expression profiles of adult schistosomes derived from yellow cattle and water buffalo by using high-throughput sequencing with Illumina Hiseq Xten. Schistosoma japonicum from water buffalo and yellow cattle yielded 63.78 million and 63.21 million reads, respectively, of which nearly 50% and 49% could be mapped to selected miRNAs in miRbase. A total of 206 miRNAs were identified, namely 79 previously annotated miRNAs of S. japonicum and 127 miRNAs that matched with the S. japonicum genome and were highly similar to the annotated miRNAs from other organisms. Among the 79 miRNAs, five (sja-miR-124-3p, sja-miR-219-5p, sja-miR-2e-3p, sja-miR-7-3p and sja-miR-3490) were significantly upregulated in the schistosomes from water buffalo compared with those from yellow cattle. A total of 268 potential target genes were predicted for these five differentially expressed miRNAs. Eleven differentially expressed targets were confirmed by qRT-PCR among 15 tested targets, one of which was further validated through dual-luciferase reporter assay. Among the 127 ‘possible’ S. japonicum miRNAs, ten were significantly differentially expressed in the schistosomes from these two hosts. CONCLUSIONS: These results highlight the important roles of miRNAs in regulating the development and survival of schistosomes in water buffalo and yellow cattle and facilitate understanding of the miRNA regulatory mechanisms in schistosomes derived from different susceptible hosts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-019-3450-7) contains supplementary material, which is available to authorized users.